Strategies of Intervention for Preterm Infants to Optimize Growth and Development - Irwanto (Departemen Ilmu Kesehatan Anak, 2017)
Preterm infants have a risk of neurodevelopmental disability including cerebral palsy, mental retardation, visual and hearing impairment, cognitive decline, speech delay, hyperkinetic disorders, behavioral and emotional disorders and learning disabilities. Similarly, parents of preterm infants also experience increased of stress, anxiety and depression in care of preterm infants. Intervention in preterm infants is to obtain outcomes of cognitive function, optimize growth and development, without behavioral disorders. Intervention strategies given to preterm infants is developmental care intervention (DCI) in hospitals and after discharge from hospital including light and sound settings, parental education, home visits, infant stimulation and kangaroo other care.